2013
DOI: 10.1177/0146167213512208
|View full text |Cite
|
Sign up to set email alerts
|

Higher Moral Obligations of Tolerance Toward Other Minorities

Abstract: In four experiments, we tested whether members of stigmatized groups are expected to be more tolerant toward other minorities than members of non-stigmatized groups and assessed the consequences of disconfirming those expectancies. Experiments 1 and 2 showed that majority group members expected members of a stigmatized group to be more tolerant toward immigrants, particularly when the stigmatized minority was perceived as having overcome the negative consequences of its victimization. When this tolerance expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 19 publications
5
36
1
Order By: Relevance
“…Learning of injustice can instigate meaning making in the form of benefit finding, implying that groups that have suffered compared to those that have not are morally obligated to refrain from harming others. The present research adds to the growing literature showing how observers restore a sense of justice after exposure to individuals who have experienced tragedy by believing that good can emerge from suffering (Anderson et al, 2010;Fernández et al, 2014;. The current studies go beyond prior work in demonstrating how the process underlying this effect-benefit finding for the victims-has consequences for groups who violate observers' expectations and engage in harm doing toward a new group.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Learning of injustice can instigate meaning making in the form of benefit finding, implying that groups that have suffered compared to those that have not are morally obligated to refrain from harming others. The present research adds to the growing literature showing how observers restore a sense of justice after exposure to individuals who have experienced tragedy by believing that good can emerge from suffering (Anderson et al, 2010;Fernández et al, 2014;. The current studies go beyond prior work in demonstrating how the process underlying this effect-benefit finding for the victims-has consequences for groups who violate observers' expectations and engage in harm doing toward a new group.…”
Section: Discussionmentioning
confidence: 59%
“…Indeed, victims themselves often report deriving benefits following traumatic experiences including learning what is really important in life and becoming a kinder, more understanding person (Affleck et al, 1987;Bower et al, 2009;Davis et al, 1998;Lazar et al, 2004;Poulin et al, 2009;Taylor, 1983). Witnesses of traumatic events can similarly make meaning of adversity by deriving benefits for the victims, which results in higher expectations that those victims will display tolerance toward others (Fernández et al, 2014). In fact, there is evidence that threat to belief in a just world is reduced, with observers exhibiting less distress, when a victim's suffering is subsequently reinterpreted as meaningful (Lazarus et al, 1965).…”
Section: Tragedy Represents a Threat To Belief In A Just Worldmentioning
confidence: 99%
See 1 more Smart Citation
“…Warner and Branscombe (2012) demonstrated that third-party observers believe victims of genocide to be morally obliged to help other victim groups. Similarly, majority group members expect members of disadvantaged minorities to be more tolerant toward other minorities such as immigrants (Fernandez, Branscombe, Saguy, Gomez, & Morales, 2014). This results in backlash against minority group members who do not express such tolerance and are judged as more immoral than members of nonstigmatized groups expressing the same attitudes (Fernandez et al, 2014).…”
Section: The Moral Obligation Trapmentioning
confidence: 99%
“…This disparity does not simply manifest in an imbalance in the appraisals of behaviours of victimized groups versus non-victimized groups. Fernandez et al (2013) found that observers extend these expectations to include the belief that members of victimized minorities (individuals with dwarfism) ought to be more tolerant of other persecuted minorities (namely gay people, immigrants). This is especially true if the victim group is perceived as having persevered to overcome a history of maltreatment.…”
Section: Perceptions Of Indigenous Moral Obligationsmentioning
confidence: 95%